2018
DOI: 10.1155/2018/3168974
|View full text |Cite
|
Sign up to set email alerts
|

Visible and Near-Infrared Reflectance Spectroscopy for Investigating Soil Mineralogy: A Review

Abstract: Clay minerals are the most reactive and important inorganic components in soils, but soil mineralogy classifies as a minor topic in soil sciences. Revisiting soil mineralogy has been gradually required. Clay minerals in soils are more complex and less well crystallized than those in sedimentary rocks, and thus, they display more complicated X-ray diffraction (XRD) patterns. Traditional characterization methods such as XRD are usually expensive and time-consuming, and they are therefore inappropriate for large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(74 citation statements)
references
References 95 publications
(141 reference statements)
5
65
0
4
Order By: Relevance
“…The measured properties include soil texture (sand, silt and clay), organic carbon (OC) and cation exchange capacity (CEC). The soil particle size was quantified by the pipette method, as described in Donagema et al (2011). The method consists of using a 0.1 M NaOH solution as a dispersing agent under high-speed mechanical stirring for 10 min.…”
Section: Data Set and Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The measured properties include soil texture (sand, silt and clay), organic carbon (OC) and cation exchange capacity (CEC). The soil particle size was quantified by the pipette method, as described in Donagema et al (2011). The method consists of using a 0.1 M NaOH solution as a dispersing agent under high-speed mechanical stirring for 10 min.…”
Section: Data Set and Chemical Analysismentioning
confidence: 99%
“…Better generalisation can be made by training the model in a larger data set. However, several studies demonstrated that the performance of the machine learning model did not increase significantly, or it even plateaued, as the calibration sample size increased (Figueroa et al, 2012;Ramirez-Lopez et al, 2014;Ng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among the clay minerals, kaolinite, montmorillonite, illite, vermiculite, and chlorite are the common clay minerals in the hydrocarbon microseepage environments. Clay minerals exhibit diagnostic absorption features near 1400 nm (caused by OH overtones), 1900 nm (overtones caused by water molecules), 2200 nm (due to Al-OH combination tones) and some weaker absorptions in the 2300-2500 nm range due to presence of Fe-or Mg-OH (Clark 1999;Zhao et al 2018;Fang et al 2018). Carbonate minerals show spectral characteristics absorption near 2350 and 2500 nm (Hunt and Salisbury, 1971).…”
Section: Re Ectance Spectroscopymentioning
confidence: 99%
“…Reflectance spectra of these 200 powder samples in 0.5 mm grain size were obtained under the same condition as the sample in Figure 2. e preprocessing method of continuum removal (CR) was employed to remove background noise of the reflectance curves and isolate particular absorption features [17].…”
Section: Spectra and Categories Acquisition Of Modeling Samplesmentioning
confidence: 99%